Biological and genomic analysis of a symbiotic nitrogen fixation defective mutant in Medicago truncatula - Shen, Yitong; Ma, Yelin; Li, Dengyao; Kang, Mingming; Pei, Yue; Zhang, Rui; Tao, Weiyu; Huang, Shenxi; Song, Wenjie; Li, Yuecheng; Huang, Wanqi; Wang, Duanyang; et al. (Frontiers in Plant Science, 2023)
Leguminous plants can form symbiotic associations with soil bacteria (collectively called rhizobia) for nitrogen fixation and with arbuscular mycorrhizal (AM) fungi for acquiring mineral nutrients such as phosphorus from soil. Consequently, legumes are widely used as an important component of sustainable agriculture (Stacey et al., 2006).However, most cultivated legume species have complex genomes and are recalcitrant to genetic transformation, thus hindering molecular genetic studies. To circumvent this problem, Medicago truncatula (M. truncatula) was selected as a model species for legume research (Barker et al., 1990). M. truncatula has several advantages for plant genomic studies over other legume species. Notably, the M. truncatula cv. Jemalong A17 genome sequence has been released (Young et al., 2011) and annotation shows more than 50,000 predicted genes or gene models (Tang et al., 2014;Pecrix et al., 2018). Determining the functions of most genes in the M. truncatula genome is a challenging task and development of diverse mutant resources is crucial for gene functional studies.To facilitate genetics and functional genomics research in this species, three mutant collections derived from ethyl methane sulfonate (EMS), fast neutron (FN) and tobacco Tnt1 retrotransposon mutagenesis have so far been developed (Penmetsa and Cook, 2000;Wang et al., 2006;Tadege et al., 2008). These genetic resources have been widely used in both forward and reverse genetic studies of regulatory genes important for development, natural product metabolisms and plant-microbe interactions (